Optical and Thermal Analysis of Secondary Optics in Light Emitting Diodes’ Packaging: Analysis of MR16 Lamp - Azarifar, Mohammad; Cengiz, Ceren; Arik, Mehmet (Journal of physics. Conference series, 2021)
Optical and thermal control are two main factors in package design process of lighting products, specifically light emitting diodes (LEDs). This research is aimed to study the role of secondary optics in opto-thermal characterization of LED packages. Novel thin total internal reflection (TIR) multifaceted reflector (MR) lens is modelled and optimized in Monte-Carlo ray-tracing simulations for MR16 package, regarded as one of the widely used LED lighting products. With criteria of designing an optical lens with 50% reduced thickness in comparison to commercially available lenses utilized in MR16 packages, nearly same light extraction efficiency and more uniform beam angles are achieved. Optical performance of the new lens is compared with the experimental results of the MR16 lamp with conventional lens. Only 2.3% reduction in maximum light intensity is obtained while lens size reduction was more than 25%. Based on the detailed CAD design, heat transfer simulations are performed comparing the lens thickness effect on heat dissipation of MR16 lamp. It was observed that using thinner lenses can reduce the lens and chip temperature, which can result in improved light quality and lifetime of both lens and light source.